A~survey on the user acceptance of PV battery storage systems - Daniel Fett; Joris Dehler-Holland; Markus Schmutz (Sustainability Management Forum, 2021)
This study presents the results of an analysis of user acceptance of PV battery storage systems. A~structural equation model is developed based on Davis' technology acceptance model (TAM). It is expanded by integrating elements of Ajzen's theory of planned behavior (TPB). The main factors influencing the acceptance of PV battery storage systems are evaluated and analyzed. Empirical findings indicate that survey participants' acceptance of PV battery storage systems is mainly influenced by their behavioral beliefs, perceived knowledge about battery storage systems, perceived ease of use, and perceived usefulness of PV battery storage systems. The results indicate a~high degree of acceptance for PV battery storage systems.
Keywords: 650; Solar energy; Battery storage; User acceptance; Technology acceptance model (TAM); Structural equation modeling (SEM)